Perceiving, Drama, Discomfort - Shadow of Disaster - Wolanin, Jerzy M. (Communications - Scientific letters of the University of Zilina, 2005)
When speaking about psychology of rescue actions there should be no restrictions to the incident only but the problem should be studied within the whole time, i.e. before, during and after the event. Disaster is irreversibly connected with a tragedy that falls deeply into social memory. Frequently it changes irrevocably the way of living of individual people and whole local population. Nonetheless, as time passes emotions connected with the disaster decrease. And even though that for various individual people the passage of time may not be of such profound importance, in the case of local population indifference grows to possible future incidents of this sort. Thus we are faced with a situation in which greatly faded emotions connected with “past” history coexist with the hope that the same thing would not take place in future. In the article this period of time is defined as a period “after-before” the disaster and is related to the period of drama and the period of discomfort.